CCL5 Suppresses Klotho Expression via p-STAT3/DNA Methyltransferase1-Mediated Promoter Hypermethylation - Liu, QiFeng; Li, ShaSha; Yu, LiXia; Yin, XiaoYa; Liu, Xi; Ye, JianMing; Lu, GuoYuan (Frontiers in Physiology, 2022)
Background Enhanced inflammation and reduced Klotho are common features in chronic kidney disease (CKD). Inflammation induces DNA hypermethylation. This study assessed the performance of inflammatory marker C-C motif chemokine 5 (CCL5) in epigenetic regulation of Klotho expression. Methods Fifty CKD patients and 25 matched controls were enrolled, and serum CCL5 level, sKlotho level, and DNA methylation were evaluated in these subjects. A renal interstitial fibrosis (RIF) model with CKD was induced in mice via unilateral ureteral obstruction (UUO) in vivo and human proximal tubular epithelial (HK-2) cells treated with CCL5 in vitro. 5-aza-2′-deoxycytidine (5-Aza), a DNA methyltransferase inhibitor was given to UUO mice. Hematoxylin and eosin (HE) and Masson trichrome staining were adopted to evaluate renal pathological changes. Methylation-specific PCR was performed to assess DNA methylation of Klotho promoter in the peripheral blood leucocytes (PBLs) from CKD patients and obstructive kidney from UUO mice. CCL5, Klotho, and DNA methyltransferases (DNMTs) were determined by ELISAs, immunofluorescence, or western blotting. HK-2 cells were exposed to CCL5 with or without 5-Aza and stattic, a p-signal transducer and activator of transcription 3 (STAT3) inhibitor, and expressions of p-STAT3, DNMT1, and Klotho were determined by western blotting. Results CCL5 upregulation concomitant with Klotho downregulation in serum and global DNA methylation in PBLs were observed in CKD samples. UUO contributed to severe renal interstitial fibrosis and enhanced expressions of fibrotic markers. Moreover, UUO increased the CCL5 level, induced Klotho promoter methylation, suppressed Klotho level, activated p-STAT3 signaling, and upregulated DNMT1 level. A similar observation was made in HK-2 cells treated with CCL5. More importantly, 5-Aza inhibited UUO-induced Klotho hypermethylation, reversed Klotho, downregulated p-STAT3 expressions, and ameliorated RIF in vivo. The consistent findings in vitro were also obtained in HK-2 cells exposed to 5-Aza and stattic. Conclusion The CCL5/p-STAT3/DNMT1 axis is implicated in epigenetic regulation of Klotho expression in CKD. This study provides novel therapeutic possibilities for reversal of Klotho suppression by CKD.